The impact of an artificial intelligence enhancement program on healthcare providers’ knowledge, attitudes, and workplace flourishing - Nofal, Hanaa A.; Mohamed, Amal E.; Almadani, Noura; Mahfouz, Rasha; Bahri, Hibah Abdulrahim; Ali, Hossam Tharwat; Elrafey, Dina S. (Frontiers in Public Health, 2025)
BackgroundThe integration of AI into healthcare influences healthcare providers’ knowledge, attitudes, and workplace flourishing, grounded in key theoretical frameworks. Social cognitive theory suggests AI-enhanced programs may shape knowledge acquisition and decision-making. The Theory of Planned Behavior helps explain how perceptions of AI affect professional attitudes. Meanwhile, workplace flourishing aligns with positive organizational psychology, emphasizing autonomy and engagement factors potentially impacted by AI adoption. We aimed to examine the impact of artificial intelligence enhancement programs on the knowledge, attitudes, and workplace flourishing of healthcare providers.MethodsThe present study was a quasi-experimental study conducted on healthcare providers at Zagazig University Hospital. The data was gathered using a self-administered three-domain tool, including an artificial intelligence knowledge domain, general attitudes toward artificial intelligence domain, and a workplace flourishing domain.ResultsRegarding the artificial intelligence technologies knowledge, attitude, and flourishing at work scales, post-intervention scores of all domains showed a statistically significant increase compared to pre-intervention, with a percent increase in knowledge score, attitude, and flourishing at work score were 123.14, 74.28, and 10.63%, respectively. Post-intervention attitude score was significantly positively correlated with knowledge score (p = 0.001). In addition, age and years of experience were negatively correlated with changes in knowledge and attitude.ConclusionArtificial intelligence training is essential for enhancing healthcare providers’ knowledge and alleviating their concerns regarding its integration into healthcare.Clinical trial registrationIdentifier PACTR202403647083094; https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=27347